International reverse knowledge transfer, absorptive capacity and the role of multinationality - Barakat, L.; Pedersen, T.; Amaral-Baptista, M.; Cretoiu, S.; Bento, P.; Rosa, A.; Serrasqueiro, R. M. (EURAM 2019 Annual Conference, 2019)
This study investigates the effect of multinationality and the variety of knowledge management mechanisms on headquarters ́ absorptive capacity in the cross-cultural reverse knowledge transfer context. We test our hypothesis on a sample of 106 Brazilian and Portuguese multinationals. Our findings show that firms that use a wide variety of knowledge transfer mechanisms globally are more capable of absorbing knowledge from their subsidiaries. Interestingly, multinationality has a positive direct effect on absorptive capacity but a negative moderating effect on the relationship between knowledge management mechanisms and the ability to absorb knowledge, which suggests that highly internationalized firms that use a wide variety of mechanisms may disperse coordination efforts, thus hindering absorptive capacity.